(untitled) (Revista Internacional de Folkcomunicação, 2020)
The photographs presented in this document belong to a section that aims to present the tradition of revelry, traditional catira dance, religious rituals and payment of promises. Feast of the Divine; Santa Tereza Community; Folia of Malaquias